Randomized Evaluation of Beta Blocker and ACE-Inhibitor/Angiotensin Receptor Blocker Treatment for Post Infarct Angina in Patients With Myocardial Infarction With Non-obstructive Coronary Arteries: A MINOCA-BAT Sub Study Rationale and Design - Pasupathy, Sivabaskari; Lindahl, Bertil; Tavella, Rosanna; Nordenskjöld, Anna M.; Zeitz, Christopher; Arstall, Margaret; Worthley, Matthew; Neil, Christopher; Singh, Kuljit; Turner, Stuart; Rajwani, Adil; Mooney, John; et al. (Frontiers in Cardiovascular Medicine, 2021)
Introduction. Myocardial infarction with non-obstructive coronary arteries (MINOCA) occurs in approximately 10% of all patients with acute myocardial infarction (AMI), with an over-representation amongst women. Remarkably, it is estimated that as many as 1 in 4 patients with MINOCA experience ongoing angina at 12 months despite having no flow-restricting stenoses in their epicardial arteries. This manuscript presents the rationale behind Randomized Evaluation of Beta Blocker and ACE-Inhibitor/Angiotensin Receptor Blocker Treatment (ACEI/ARB) for Post Infarct Angina in MINOCA patients – The MINOCA BAT post infarct angina sub study. Methods. This trial is a registry-based, randomized, parallel, open-label, multicenter trial with 2x2 factorial design. The primary aim is to determine whether oral beta blockade compared with no oral beta-blockade, and ACEI/ARB compared with no ACEI/ARB, reduce post infarct angina in patients discharged after MINOCA without clinical signs of heart failure and with left ventricular ejection fraction ≥40%. A total of 664 patients will be randomized into four groups; (i) ACEI/ARB with beta blocker, (ii) beta blocker only, (iii) ACEI/ARB only, or (iv) neither ACEI/ARB nor beta blocker and followed for 12 months. Results. The trial is currently recruiting in Australia and Sweden. 56 patients have been recruited thus far. Both sexes were equally distributed (52% women and 48% men) and the mean age was 56.3±9.9 years. Conclusions. It remains unclear whether conventional secondary preventive therapies are beneficial to MINOCA patients in regard to post infarct angina. Studies of routine clinical practice suggest that use of secondary prevention therapies are less likely to be used in MINOCA patients. Thus, results from this trial will provide insights for future treatment strategies and guidelines specific to MINOCA patients.